Clinical and demographic characteristics of male patients with Brucellar epididymo-orchitis: a retrospective cohort study from an endemic region - Mazor, Elad; Smolyakov, Rozalia; Hazan, Itai; Yusim, Igor; Novack, Victor; Herzberg, Haim; Mabjeesh, Nicola J.; Zohar, Yarden (Frontiers in Microbiology, 2025)
BackgroundBrucellar epididymo-orchitis (BEO) is an under-recognized complication of brucellosis, which can have long-term consequences. This study aimed to identify clinical and demographic factors associated with BEO among male patients in a highly endemic population.MethodsWe conducted a retrospective analysis of patients diagnosed with brucellosis confirmed by positive serological assays at our medical center. The demographic and clinical characteristics of patients with BEO were compared with those of patients with brucellosis but without epididymo-orchitis (EO).ResultsBetween 2001 and 2019, 2,422 individuals presented with brucellosis. Of these, 39 (1.6%) had BEO, and 2,383 had non-EO brucellosis. Most patients in both groups were of the Bedouin ethnicity (90%–94%). A comparison of age, BMI, and number of children revealed statistically significant differences. To minimize bias, a 1:3 matched comparison was performed between 117 non-EO brucellosis patients and 39 BEO patients. This comparison showed that patients with BEO had a significantly lower number of children (median of 2 vs. 6). In terms of laboratory findings, patients with BEO had a significantly higher C-reactive protein (CRP) level (median, 11 vs. 1.8). No differences were found in environmental risk factors, such as smoking.ConclusionBEO patients were older, had higher BMI and inflammatory markers, and reported fewer children compared to non-EO brucellosis patients. These findings may reflect delayed diagnosis or chronicity, though reproductive implications remain speculative and warrant prospective evaluation.